Examining the determinant factor of football technical skills - Panuwun Joko Nurcahyo; Kusnandar Kusnandar; Didik Rilastiyo Budi; Arfin Deri Listiandi; Erwin Oliver Estrella; Mohhamad Ashraf Khan; Mohammed Asim Ghazi; Mazuki Mohd Yasim; Mohd Izwan Shahril (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Introduction: Football sport has various factors that affect achievement, including physical condition, technique, tactics and mentality.